Idiomatic Translation in the Story of some Words with a Mummy - Thomas Leonardi; Riris Mutiara Paulina Simamora; Adrallisman (e-LinguaTera, 2025)
One issue faced in translating a text is idioms. Idiomatic expressions are special which required extra work and cautiousness to discover the true meaning of the authors' intentions. This study aims to analyse the translation of idioms which found in Edgar Allan Poe's short story Some Words With A Mummy, translated by Maggie Tiojakin under the translation title Obrolan Dengan Mummy. This research is a qualitative descriptive study. The data are English idioms and their translation in Indonesian. There are 15 data. Those are analyzed based on Nida and Taber's idiom translation strategies. They are (1) idioms are translated into non-idioms, (2) idioms are translated into idioms, and (3) on-idioms are translated into idioms. The result shows that there are three strategies of English idioms translation in Edgar Allan Poe's short story Some Words With A Mummy. They are (1) translation idioms to idioms (27 %), (2) translation idioms to non-idioms (67 %), and (3) translation non-idioms to idioms (7 %) and the most dominant strategy is a translation by idioms to non-idioms.